ANALISIS HUKUM KOMPETENSI ANGGOTA SAMAPTA POLRES SORONG KOTA DALAM MELAKSANAKAN TUGAS TINDAKAN PERTAMA TEMPAT KEJADIAN PERKARA LALU LINTAS - Sartono Fabanyo; Raymond R Morintoh; Weron Murary (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The aim of this research is that the police, as public servants, are expected to perform their duties more professionally and independently. Therefore, in serving the community, they must be ready to help whenever a problem arises. Samapta is a technical police function that carries out preventive tasks to create a conducive security situation by providing protection, guidance, and services to the community. Samapta is often associated with patrols, being present among the people, especially in activity centers, residential areas, and places that require police presence. The competence of Samapta members at the Sorong City Police in carrying out first-response duties at traffic incident sites aims to evaluate how the Samapta members perform their duties according to existing legal regulations, particularly at the Sorong City Police. The practice of handling accidents starts after receiving reports or complaints from the public. Then, some officers will immediately head to the scene to check the report and carry out crime scene processing. The research used is normative-empirical research, which will be carried out by gathering information in the field (Field Research). Normative-empirical research is used to analyze or find out how far regulations or laws are being effectively implemented. Therefore, the research location chosen is at the Sorong City Police Department in Southwest Papua Province. Based on the source, data is divided into two types: primary data, which is data created by the researcher for a specific purpose to solve the problem being handled directly by the researcher from the first source or the place where the research object is conducted, related to the competence of Samapta Polres Sorong members; and secondary data, which is data that has been collected for purposes other than solving the current problem, from literature, articles, journals, and websites on the internet related to the research, to provide explanations, seek interpretations from respondents, or draw conclusions. The authority of Samapta Polres Sorong Kota members in carrying out initial actions at traffic crime scenes emphasizes that Samapta acts as first responders who maintain security, provide assistance, and manage traffic around the scene. Samapta's authority is limited to securing and handling the initial situation, not investigating. The legal process afterward remains the responsibility of the Traffic and Criminal Investigation units. Cross-functional coordination is very important so that handling the crime scene is effective, fast, and according to legal procedures. The role of Samapta can be optimized through ongoing training, improved facilities, and synergy between units at Polres Sorong Kota. Improving the competence of Samapta members at Sorong City Police in handling traffic crime scenes involves a combination of continuous training, adequate facilities, clear SOPs, and cross-unit coordination. With these steps, handling traffic accidents will be more professional, faster, and lawful, directly impacting public safety and the police's image.Keywords: Samapta, Sorong City Police, Competence, Traffic Incidents.